Decarbonization Policy in the Eurasian Economic Union: Meeting the Challenge of Global Climate Change (comparative analysis) - Davtyan, Vahe; Khachikyan, Silva (YSU Journal of International Affairs, 2024)
The article examines the issues of decarbonization in the member states of the Eurasian Economic Union in the context of global challenges of climate change. The international regime for reducing greenhouse gas emissions into the atmosphere is analyzed. Its impact on the global political agenda is determined. It is established that one of the main challenges to reducing emissions is the development of "green" types of energy, which should be understood as not only renewable energy sources, but also natural gas and nuclear energy. Through a comparative analysis of both energy systems and national programs for reducing greenhouse gas emissions of the EAEU member states, their potential for implementing the "energy transition" and decarbonization is determined. The challenges of economic development in the EAEU are shown through the prism of the Paris Agreement on Climate Change. Recommendations are given for improving cooperation between the EAEU member countries in the field of decarbonization and synchronizing strategic approaches in the field of climate management and sustainable development.